Type a personality and nutritional behaviours of competitive basketball players - Gacek, M.; Wojtowicz, A.; López Sánchez, G. F. (Journal of Kinesiology and Exercise Sciences, 2024)
Introduction. Type A personality pattern (TAPP) is related to, among others, strong rivalry and struggle for achievements, which are features that fit into sports competition. One of the determinants of sports success is a proper diet. The aim of the study was to assess the relationship between the level of type A personality behavioural pattern and nutritional behaviours of basketball players.